Optimization of post-PCI outcomes: the role of early rehabilitation in cardiopulmonary recovery and life satisfaction in patients with heart failure - Chowdhury, Ziaur Rahman; Shoma, Farzana Khan; Nadim Kamal, M.; Imamur Rashid, M.; Abul Kalam Azad, M.; Rahman, Nadia; Shabnam, Mita; Islam, Mohammad Asraful; Moniruzzaman Khan, M. (International Journal of Research in Medical Sciences, 2024)
Background: Early rehabilitation following percutaneous coronary intervention (PCI) in heart failure patients may enhance cardiopulmonary recovery and quality of life while reducing hospital readmissions and complications. This study aimed to evaluate the impact of early rehabilitation on post-PCI outcomes. Methods: A total of 50 patients with heart failure who underwent PCI were enrolled and divided into two groups: the early rehabilitation group (n=25) received a structured rehabilitation program, while the control group (n=25) received standard post-PCI care. Key outcomes, including cardiopulmonary function, quality of life, hospital readmissions, and complications, were assessed over a 6-month period. Results: Significant improvements in cardiopulmonary function were observed in the early rehabilitation group. Ejection fraction increased from 40.5±7.8% to 47.1±5.9% (p=0.001), VO2 max improved from 16.1±4.1 to 21.2±3.5 ml/kg/min (p=0.003), and the 6-minute walk distance increased by 64.5 meters (p=0.004). Quality of life improved, with SF-36 physical and mental health scores rising by 30% and 34%, respectively, and the MLHFQ score decreasing by 17 points (p=0.002). Hospital readmissions and major cardiovascular events were significantly lower in the early rehabilitation group (p=0.040 and p=0.031, respectively). Conclusions: Early rehabilitation significantly improves cardiopulmonary function and quality of life while reducing hospital readmissions and complications in heart failure patients post-PCI. These findings highlight the importance of incorporating structured rehabilitation into post-PCI care to optimize recovery.